2005
DOI: 10.2527/2005.83102303x
|View full text |Cite
|
Sign up to set email alerts
|

Divergent selection for uterine capacity in rabbits. II. Correlated response in litter size and its components estimated with a cryopreserved control population1

Abstract: Our objective was to evaluate the correlated responses to selection for litter size and its components after 10 generations of divergent selection for uterine capacity (UC). A total of 294 intact females from the 11th and 12th generations of divergent selection for high and low UC and from a cryopreserved control population was used (139, 112, and 43 females, respectively). Uterine capacity was assessed as litter size in unilaterally ovariectomized females. Traits recorded on females for up to five parities we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
39
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 19 publications
9
39
0
2
Order By: Relevance
“…In conclusion, the present study provides a list of candidate genes differentially expressed in the oviduct of two lines of rabbits divergently selected for UC. The genes overexpressed in the L line seem to be related to a decrease of early embryo development and survival, in agreement with previous results found in this line Mocé et al 2005;Santacreu et al 2005;Peiró et al 2007). However, further studies are necessary to elucidate the relevance of those genes and proteins on rabbit reproductive traits.…”
Section: Ssh Librariessupporting
confidence: 89%
See 1 more Smart Citation
“…In conclusion, the present study provides a list of candidate genes differentially expressed in the oviduct of two lines of rabbits divergently selected for UC. The genes overexpressed in the L line seem to be related to a decrease of early embryo development and survival, in agreement with previous results found in this line Mocé et al 2005;Santacreu et al 2005;Peiró et al 2007). However, further studies are necessary to elucidate the relevance of those genes and proteins on rabbit reproductive traits.…”
Section: Ssh Librariessupporting
confidence: 89%
“…However, when only RT-qPCR expression values from the females used for SSH construction (3 from each line) were analyzed, both genes exhibited higher levels of expression (1.5 fold and 2-fold increase in OVGP1 and ANXA1 expression, respectively) in the H line compared with the L line (data not shown). Several factors may explain this result including: 1) a sampling effect in the selection of the animals for SSH, 2) the inclusion in the RT-qPCR analysis of animals with less extreme phenotypes or 3) divergent selection for UC was more effective in the L line than in the H line (Argente et al 1997;Santacreu et al 2005;Mocé et al 2005) and hence, animals from the H line showed more variability in gene expression because they may be less genetically uniform than L animals. Of the 3 validated genes by RT-qPCR from L line, HSD17B4 and PGR are involved in "reproductive development process".…”
Section: Ssh Librariesmentioning
confidence: 99%
“…This difference was approximately half of the difference found using intact does (2.35 kits; Santacreu et al 2005).…”
Section: Discussionmentioning
confidence: 77%
“…The high (H) line showed a higher litter size (2.35 kits in intact females) and also a higher number of embryos before implantation (1.8 embryos in intact females) than the low (L) line . This difference was not due to a higher ovulation rate (Mocé et al 2002;Santacreu et al 2005) or fertilization rate (Santacreu et al 1996), both of which were similar in both lines. A difference of 1 embryo between lines was observed at 72 hr of gestation in favor of the H line, using intact does (Mocé et al 2004).…”
mentioning
confidence: 88%
See 1 more Smart Citation